Transcriptomics of induced defense responses to greenbug aphid feeding in near isogenic wheat lines. - Reddy, Srirama Krishna; Weng, Yiqun; Rudd, Jackie C.; Akhunova, Alina R.; Liu, Shuyu (My University, 2014)
The greenbug aphid, Schizaphis graminum (Rondani) is an important cereal pest, periodically threatening wheat yields in the United States and around the world. The single dominant gene, Gb3-based resistance is highly durable against prevailing greenbug biotypes under field conditions; however, the molecular mechanisms of Gb3-mediated defense responses remain unknown. We used Affymetrix GeneChip Wheat Genome Arrays to investigate the transcriptomics of host defense responses upon greenbug feeding on resistant and susceptible bulks (RB and SB, respectively) derived from two near-isogenic lines. The study identified 692 differentially expressed transcripts and further functional classification recognized 122 transcripts that are putatively associated to mediate biotic stress responses. In RB, Gb3-mediated resistance resulted in activation of transmembrane receptor kinases and signaling-related transcripts involved in early signal transduction cascades. While in SB, transcripts mediating final steps in jasmonic acid biosynthesis, redox homeostasis, peroxidases, glutathione S-transferases, and notable defense-related secondary metabolites were induced. Also transcripts involved in callose and cell wall decomposition were elevated SB, plausibly to facilitate uninterrupted feeding operations. These results suggest that Gb3-mediated resistance is less vulnerable to cell wall modification and the data provides ample tools for further investigations concerning R gene based model of resistance.
Keywords: Aphid resistance; Greenbug; Jasmonic acid; Microarray; Transcriptomics; Wheat